Pemanfaatan Bunga Melati Putih (Jasminum sambac) dalam Upacara Adat Masyarakat Kota Serang - Nurjannah, Ijah; Vanza, Nabila; Rahayu, Sri; Amelia, Evi; Fitriana, Desi Eka Nur (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2025)
White jasmine (Jasminum sambac) holds strong symbolic and cultural value in various traditional ceremonies in Serang City. This study aims to examine its ethnobotanical role and conservation efforts to preserve its cultural significance and ecological sustainability. A descriptive qualitative method was used with purposive sampling, involving experienced jasmine flower artisans as participants. Data were collected through in-depth interviews, field observations, and documentation, then analyzed qualitatively. The results show that white jasmine is used in wedding rituals, purification ceremonies, funerals, and offerings—reflecting spiritual, aesthetic, and medicinal meanings. Its morphological features and active compounds such as linalool and benzyl acetate support its role in tradition and healing. Conservation efforts include sustainable cultivation, public education, and reinforcing cultural values in environmental preservation. This study underscores the importance of integrating cultural heritage and biodiversity conservation to maintain local flora as part of intangible cultural assets.